Sustainable healthcare - Schroeder, Knut.; Wiley eBooks (Chichester, West Sussex : John Wiley & Sons, 2013)
Containing case studies and resources for further information and action, this book is a practical guide to making healthcare more sustainable for healthcare professionals, managers, and students.
Greening the gaze -- Climate science in context -- Engaging with sustainability -- A vision for sustainable healthcare -- Low-carbon clinical care -- Food for people and planet -- Travel and transport : moving to better health -- Healthy buildings, healthy spaces -- Resource stewardship -- The green death -- The green academy -- The journey towards sustainable healthcare.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Medical care -- Environmental aspects; Medicine -- Environmental aspects; Delivery of Health Care; Climate Change; Conservation of Natural Resources; HEALTH & FITNESS -- Diseases -- General; HEALTH & FITNESS -- Health Care Issues; MEDICAL -- Diseases; MEDICAL -- Health Care Delivery; MEDICAL -- Health Policy; MEDICAL -- Public Health; SOCIAL SCIENCE -- Disease & Health Issues; Electronic books